1991
DOI: 10.1051/agro:19911007
|View full text |Cite
|
Sign up to set email alerts
|

Crown gall incidence in plant nurseries of Algeria, characteristics of Agrobacterium tumefaciens strains, and biological control of strains sensitive and resistant to agrocin 84

Abstract: Summary ― Crown gall was observed in 99% of the plant nurseries surveyed in the major fruit tree production region of Algeria. Among 11 tree species surveyed, those with highest disease incidence were peach (5.39%), almond (3.43%), cherry (1.50%), apple (1.47%), and olive (1.30%). None

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
3

Year Published

1993
1993
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
1
7
0
3
Order By: Relevance
“…They are usually responsible for gall disease in vegetables. This bacterium was also found by Bouzar et al [22], who showed that the fruits in tree nurseries of Algeria were infected by this germ and the most affected botanical species were peach tree, almond tree, cherry tree, apple tree and olive tree.…”
Section: Analysis Of Pcr-dgge Profilessupporting
confidence: 73%
“…They are usually responsible for gall disease in vegetables. This bacterium was also found by Bouzar et al [22], who showed that the fruits in tree nurseries of Algeria were infected by this germ and the most affected botanical species were peach tree, almond tree, cherry tree, apple tree and olive tree.…”
Section: Analysis Of Pcr-dgge Profilessupporting
confidence: 73%
“…Selective isolation of bv. 1 and/or pseudomonads by this medium has been reported elsewhere (5,10). It should be noted, however, that RS and MG media were useful in complementing the other two media for the isolation of additional strains, some of which had peculiar chromosome and plasmid phenotypes.…”
Section: Discussionmentioning
confidence: 65%
“…This paucity of information is due in part to the rare detection of tumorigenic strains in the soil and on roots, even though nontumorigenic agrobacteria are commonly found (2,7,10,35,52). These apparently low levels of tumorigenic bacteria in soil are in sharp contrast to the regular occurrence of crown gall epidemics and the efficacious protection against soil infections by the biocontrol agent K84 (5,35).…”
mentioning
confidence: 87%
“…Ainsi, le pourcentage de souches sensibles à K 84 est plus élevé chez le biovar 2 (92%) que le biovar 1 (71%), alors qu'il reste élevé (92 -97%) pour la K 1026 pour les deux biovars. Ces résultats sont différents de ceux obtenus par Schroth & Moller (1976), López et al (1989) et Bouzzar et al (1991 avec la K 84 et nous estimons que l'utilisation du milieu MG dans notre travail a augmenté la qualité de l'antagonisme in vitro par rapport au milieu de Stonier (1960) utilisé par ces auteurs. La K 1026 est d'utilisation récente, datant des années 1998.…”
Section: Influence Du Biovarunclassified